Knowledge Graph Construction for Big Data Management and Applications Based on RoBERTa-BiLSTM-CRF Modeling - Yan, Li; Tao, Huang; Xiang, Li (2024 International Conference on Intelligent Computing and Next Generation Networks (ICNGN), 2024)
With the increasing requirements for the development and utilization of big data, it becomes more and more important to cultivate big data talents to meet the needs of society. The traditional information literacy talent cultivation program can no longer meet the needs of the society for big data talents. Existing big data management majors focus their curriculum construction on the construction of core courses. They do not pay attention to the correlation between the knowledge points in different core courses. In this paper, we propose a professional knowledge mapping method based on RoBERTa-BiLSTM-CRF model for big data management applications, which can effectively solve the above problems, and can more accurately identify the management relationship between the knowledge points in the core courses, help learners better understand and memorize the knowledge, and then establish the linkage of knowledge and the overall framework.